2023
DOI: 10.1021/acsomega.3c00933
|View full text |Cite
|
Sign up to set email alerts
|

New Natural Eugenol Derivatives as Antiproliferative Agents: Synthesis, Biological Evaluation, and Computational Studies

Abstract: Semisynthetic modifications of natural products have bestowed us with many anticancer drugs. In the present work, a natural product, eugenol, has been modified synthetically to generate new anticancer agents. The final compounds were structurally confirmed by NMR, IR, and mass techniques. From the cytotoxicity results, compound 17 bearing morpholine was found to be the most active cytotoxic agent with IC 50 1.71 (MCF-7), 1.84 (SKOV3), and 1.1 μM (PC-3) and a thymidylate synthase (TS) inhibitor with an IC 50 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The molecular electrostatic potential (MEP), in the qualitative interpretation of chemical reactivity has a long history [45] . That can provide useful insights into the reactivity and selectivity of chemical reactions [46] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular electrostatic potential (MEP), in the qualitative interpretation of chemical reactivity has a long history [45] . That can provide useful insights into the reactivity and selectivity of chemical reactions [46] .…”
Section: Resultsmentioning
confidence: 99%
“…The molecular electrostatic potential (MEP), in the qualitative interpretation of chemical reactivity has a long history. [45] That can provide useful insights into the reactivity and selectivity of chemical reactions. [46] It shows the spatial variation of electrostatic potential around a molecule, which reflects the electronic structure and shape of the molecule.…”
Section: Molecular Electrostatic Potential (Mep)mentioning
confidence: 99%
“…The docking analysis was performed to explicate the potency of these desirable molecules in vitro against the EGFR, MMP-2, and hCAII proteins, respectively, through their potential interaction mechanisms with their crystal frameworks (PDB: 4HJO [77], 1HOV [78], 3M04 [79]). The docking investigation procedures were implemented using Glide's module ® [80][81][82][83][84]. The preliminary inhibitors (Erlotinib, hydroxamic acid, and sulfonamide) were redocked into the examined crystal frameworks to verify the docking methodology.…”
Section: Molecular Docking Analysismentioning
confidence: 99%
“…16–18 To synthesize eugenol-based heterocyclic derivatives with interesting activities, Syed Nazreen's team developed new 1,3,4-oxadiazole heterocycles with anticancer properties. 19 Similarly, Abdelmaoujoud Taia and colleagues have synthesized new heterocycles, 1,2,3-triazoles, with anticorrosive activity, particularly for iron in acid solutions. 20 Moreover, heterocyclic pyrrole compounds, characterized by a five-membered ring comprising four adjacent carbon atoms and one nitrogen atom, have recently been prepared by Sergei Boichuk et al 21 These products have found wide therapeutic applications 21,22 due to their diverse biological properties, 23 including antimicrobial 24 and anticancer activities.…”
Section: Introductionmentioning
confidence: 99%